Exploring Devayan Language Maintenance among Parents in Simeulue Regency, Indonesia - Yesi Oresah; Idaryani Idaryani; Safriandi Safriandi (FKIP Universitas Palangka Raya, 2026)
This study examines the parents’ efforts and their attitudesto maintain Devayan language withinnon-formaldomain. and factors that influence the preservation of the Devayan language among parentsin Simeulue Regency, Indonesian. Drawing on qualitative descriptive methods, data were collected through semi-structured interviews and observation, involving six Devayan-speaking parents. The findings demonstrated that Devayan remains actively maintained through consistent intergenerational transmission to their children, positive parental language attitudes, and dense local speech networks that extend beyond the household into neighborhoods, markets, and social gatherings. Parents play a central role by establishing Devayan as the dominant home language, modelling consistent speaking the Devayan with their children, and embedding language use within culturally meaningful activities. Parents are highly aware of the importance of passing on the Devayan language to their children as a cultural heritage that must be preserved. These practices position Devayan not merely as a communicative tool, but as a marker of identity for Devayan community. The study contributes to heritage language maintenance by highlighting the synergistic relationship between parents’ consistency and community-level validation in language use. The findings suggest that effective language maintenance emerges from everyday practices grounded in affective commitment of parents to their children, cultural transmission, and adaptive bilingualism. Kata Kunci Language maintenance, Devayan language, Parents